An Examination of the Evidence-Base of School-Wide Positive Behavior Interventions and Supports Through Two Quality Appraisal Processes. (October 2018) - Mitchell, Barbara S.; Hatton, Heather; Lewis, Timothy J.
Thousands of schools across the United States, and worldwide, implement School-Wide Positive Behavioral Interventions and Supports (SWPBIS). SWPBIS provides a framework whereby teams of educators engage in data-based decision making to select, implement, and monitor a continuum of behavioral supports and build sustainable systems to promote implementation fidelity among school staff. To date, a large body of research supports both the essential practices included in a SWPBIS framework as well as the larger systemic approach. Recently public policy and professional organization guidelines have outlined clear appraisal processes to review the extant literature in an effort to designate interventions as "evidence-based." This review applied both the What Works Clearinghouse (WWC) and the Council for Exceptional Children (CEC) standards to evaluate existing group experimental design studies of SWPBIS. Results identified five unique, group design studies conducted by four separate research teams. Four of the studies met the WWC design standards "without reservations" and findings from three of those studies were characterized as positive. Outcomes from the reviewed studies indicated that when provided with training in components of SWPBIS, school teams met minimal implementation standards. In addition, schools that met implementation criteria also saw positive changes in school climate, staff perceptions, and/or student behaviors. However, application of the CEC standards resulted with a rating of "insufficient evidence" because none of the five studies met all CEC quality indicators. These studies lacked report of implementation fidelity for the SWPBIS training provided, which was the independent variable. Implications for practice and future research are discussed.